Probing the Domain Architecture in 2D α‐Mo2C via Polarized Raman Spectroscopy. Issue 8 (7th January 2019) - Li, Tianshu; Luo, Weijun; Kitadai, Hikari; Wang, Xingzhi; Ling, Xi
Abstract: MXenes are emerging 2D materials with intriguing properties such as excellent stability and high conductivity. Here, a systematic study on the Raman spectra of 2D α‐Mo2 C (molybdenum carbide), a promising member in MXene family, is conducted. Six experimentally observed Raman modes from ultrathin α‐Mo2 C crystal are first assigned with the assistance of phonon dispersion calculated from density functional theory. Angle‐resolved polarized Raman spectroscopy indicates the anisotropy of α‐Mo2 C in the b – c plane. Raman spectroscopy is further used to study the unique domain structures of 2D α‐Mo2 C crystals grown by chemical vapor deposition. A Raman mapping investigation suggests that most of the α‐Mo2 C flakes contain multiple domains and the c ‐axes of neighboring domains tend to form a 60° or 120° angle, due to the weak MoC bonds in this interstitial carbide and the low formation energy of the carbon chains along three equivalent directions. This study demonstrates that polarized Raman spectroscopy is a powerful and effective way to characterize the domain structures in α‐Mo2 C, which will facilitate the further exploration of the domain‐structure‐related properties and potential applications of α‐Mo2 C. Abstract : The Raman spectra of 2D α‐Mo2 C (molybdenum carbide) crystal is systematically studied. Six experimentally observed Raman modes of 2D α‐Mo2 C are assigned for the first time. Angleresolved polarized Raman spectroscopy indicates the in‐plane anisotropy of α‐Mo2 C. Raman mapping reveals the unique domain structures of α‐Mo2 C flakes grown by chemical vapor deposition.